Coded space-time-frequency OFDM over IEEE 802.11 fading channels - Nor Kamariah, Noordin, Dr.; Borhanuddin, Mohd. Ali, Prof. Dr.; Jamuar, Sudhanshu Shekhar, Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/